Aquinas's Summa : background, structure, & reception - Torrell, Jean-Pierre. (Washington, D.C. : Catholic University of America Press, 2005)
"In this concise new volume by the acclaimed author of the biography of Saint Thomas Aquinas, Jean-Pierre Torrell brings his expertise to bear on Aquinas's Summa Theologiae. Torrell begins with an expert account of Aquinas's life and then turns his attention to the overall structures and specific content of the Summa. He considers the literary and doctrinal context of the Summa, situating the work within the overall literary corpus of the Angelic Doctor and examining Aquinas's Christian, Greek, Jewish, and Arab sources." "The second half of the book surveys the history of the Summa's influence from Aquinas's death in 1274 through the twentieth century. Torrell traces the fate of Aquinas's Summa from its slow start, through the eventual emergence of Thomism, to its widespread acceptance. The nineteenth and twentieth centuries witnessed the ultimate triumph of Aquinas's work with the encyclical Aeternis patris, and in the wake of Vatican II there has been renewed interest in its content and method."--BOOK JACKET.
I. The author and his work -- II. The Summa : structures and content I -- III. The Summa : structures and content II -- IV. The literary and doctrinal milieu -- V. The Summa through history -- VI. The Summa in the twentieth century.
Includes bibliographical references (p. 135-138) and index.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Catholic Church -- Doctrines; Theology, Doctrinal